2024
DOI: 10.1002/path.6240
|View full text |Cite
|
Sign up to set email alerts
|

A partial epithelial‐mesenchymal transition signature for highly aggressive colorectal cancer cells that survive under nutrient restriction

Gil A Pastorino,
Ilir Sheraj,
Kerstin Huebner
et al.

Abstract: Partial epithelial‐mesenchymal transition (p‐EMT) has recently been identified as a hybrid state consisting of cells with both epithelial and mesenchymal characteristics and is associated with the migration, metastasis, and chemoresistance of cancer cells. Here, we describe the induction of p‐EMT in starved colorectal cancer (CRC) cells and identify a p‐EMT gene signature that can predict prognosis. Functional characterisation of starvation‐induced p‐EMT in HCT116, DLD1, and HT29 cells showed changes in prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
(87 reference statements)
2
3
0
Order By: Relevance
“…RNA sequencing analysis of the nutrient rich (NR) and ND Caco-2 cells, which showed the highest EMT score, revealed the activation of autophagy, cell cycle arrest and a decrease in energy generating pathways with ND, as expected, while at the same time differentially regulating a highly connected network of EMT related genes. This network had EGFR and SERPINE1 at its hub, supporting a recent three gene p-EMT signature consisting of EGFR, SERPINE 1 and SOX10 that we identified in nutrient depleted HCT116 cells, which could significantly predict worse disease-free survival (DFS) in multiple CRC patient cohorts [ 28 ]. CRC tumors showing the three gene signature were categorized as Consensus Molecular Subtype (CMS) 4, associated with a metastatic and invasive phenotype [ 36 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…RNA sequencing analysis of the nutrient rich (NR) and ND Caco-2 cells, which showed the highest EMT score, revealed the activation of autophagy, cell cycle arrest and a decrease in energy generating pathways with ND, as expected, while at the same time differentially regulating a highly connected network of EMT related genes. This network had EGFR and SERPINE1 at its hub, supporting a recent three gene p-EMT signature consisting of EGFR, SERPINE 1 and SOX10 that we identified in nutrient depleted HCT116 cells, which could significantly predict worse disease-free survival (DFS) in multiple CRC patient cohorts [ 28 ]. CRC tumors showing the three gene signature were categorized as Consensus Molecular Subtype (CMS) 4, associated with a metastatic and invasive phenotype [ 36 ].…”
Section: Discussionsupporting
confidence: 79%
“…The colony formation assay indicated that the number of colonies formed in the NR medium was statistically similar to the number of colonies formed in the ND medium, indicating high viability. We have previously reported similar changes in ND T84 [25] , HT-29 and DLD1 cells [ 28 ]. High cell survival was corroborated by the CAM assay, whereby Caco-2, HCT116 and LoVo cells incubated in the ND medium were capable of forming tumors with comparable size and volume to the cells incubated in the NR medium.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Tailoring precision medicine approaches to the specific molecular profile of an individual patient’s tumor requires a comprehensive understanding of the unique molecular characteristics of each subtype. The challenge lies in developing therapies that are effective across the spectrum of colorectal cancer subtypes while avoiding generalized approaches that may not be equally beneficial for all patients. , …”
Section: Challenges and Considerations In Precision Medicine Implemen...mentioning
confidence: 99%
“…The challenge lies in developing therapies that are effective across the spectrum of colorectal cancer subtypes while avoiding generalized approaches that may not be equally beneficial for all patients. 178,179 The evolution of resistance and issues related to drug specificity underscore the need for a dynamic and adaptable approach in precision medicine implementation against colorectal cancer. Continuous monitoring of a patient's molecular profile throughout the course of treatment, incorporating real-time data, and utilizing advanced diagnostic technologies become crucial components of a successful precision medicine strategy.…”
Section: Integration Of Biomarkermentioning
confidence: 99%